Genetic predisposition to persistent fatigue after a diagnosis of colorectal cancer - Kazemian, Elham; Mo, Qianxing; Matejcic, Marco; Tsai, Ya-Yu; Sobieski, Daniel; Li, Xiaoyin; Hoogland, Aasha I.; Crowder, Sylvia L.; Gonzalez, Brian D.; Oswald, Laura B.; Sleight, Alix G.; Nguyen, Nathalie; et al. (Journal of the National Cancer Institute, 2025)
Cancer-related fatigue (fatigue) is a common and persistent symptom after cancer treatment, yet the role of genetic susceptibility remains unclear.We used data from a prospective cohort study called the ColoCare Study, conducted over 5 US sites and Germany. Fatigue was assessed at 5 time points using the European Organisation for the Research and Treatment of Cancer Core Quality of Life Questionnaire fatigue subscale and analyzed as (1) a binary summary measure of the trajectory from diagnosis into survivorship (defined as severe: yes/no), (2) a mean score across all time points, and (3) the highest (ie, worst) score across all time points. We genotyped samples using the Illumina Infinium Global Diversity Array kit with imputation using the National Institutes of Health TOPMed reference panel to conduct a genome-wide association study. The Sum of Single Effects was used to identify independent secondary signals. Transcriptome-wide association studies using the S-PrediXcan and MultiXcan methods were conducted to examine genetic regulation of gene expression. The COLOC package assessed whether variants identified in the genome-wide association study influence gene expression through colocalization analysis.Among 1219 participants, 31.0% experienced severe fatigue over the course of their disease. A locus near LINC02505 on chromosome 4 was associated with severe fatigue (rs6531463; odds ratio = 3.25, P = 3.88 × 10−8). When modeling mean fatigue levels, strongly associated variants were identified in or near NEK10 and SLC4A7. Integrative analyses linked the predicted expression of NEK10 in liver tissue to risk of fatigue (P < 4.36 × 10−6). Colocalization analysis identified genetic loci and gene expression near NEK10 (posterior probabilities >0.9).This study identified novel genetic loci associated with fatigue in patients with colorectal cancer and may be useful for identifying high-risk individuals for preventative strategies.